In the I of the beholder: an attempt to capture the implicit self-concept regarding psychopathy - Krüppel, Jonas; Yoon, Dahlnym; Zerres, Katharina; Brunner, Franziska; Mokros, Andreas (Frontiers in Psychology, 2024)
This article explores the implicit self-concept pertaining to psychopathy. Two online studies showed inconsistent results, with Study 1 (n = 243) suggesting that psychopathy is linked to an implicit self-concept marked by low empathy and Study 2 (n = 230) implying no such relationship. In a sample of offenders and community controls (Study 3a, n = 166), higher scores on the Psychopathy Checklist-Revised (PCL-R) were related to an implicit self-concept of being less rather than more antisocial, and the implicit self-concept showed incremental validity compared to the explicit self-concept. The retesting of an offender subsample (Study 3b, n = 47) yielded no evidence for temporal stability or convergent validity. The implicit self-concept of highly-psychopathic individuals thus appears to vary, depending on the social context. Future studies should replicate these results in different samples, using additional external correlates.